The serotonin transporter genotype modulates the relationship between early stress and adult suicidality in bipolar disorder. (15th September 2014) - Benedetti, Francesco; Riccaboni, Roberta; Poletti, Sara; Radaelli, Daniele; Locatelli, Clara; Lorenzi, Cristina; Pirovano, Adele; Smeraldi, Enrico; Colombo, Cristina
<x xml:space="preserve">Abstract</x> Objective Bipolar disorder (BD) is associated with a higher risk of suicide and with worse early life stress. A serotonin (5‐hydroxytryptamine; 5‐HT) transporter‐linked polymorphic region (5‐HTTLPR) has been shown to influence the relationship between stress and the risk of attempting suicide in the general population, but has not been investigated in BD. Methods We studied 136 inpatients (93 females, 43 males) with a major depressive episode in the course of BD. Early and recent stressful life events were scored on the Social Readjustment Rating Scale (SRRS). Regional gray matter (GM) volumes were analyzed, acquiring T1‐weighted images on a 3.0 Tesla scanner. Results Homozygote l/l patients attempted suicide in a higher proportion than *s carriers. A separate‐slopes logistic regression showed a significant effect of 5‐HTTLPR on the relationship between stress, depression, and suicide among *s carriers, but not among l/l homozygotes, early stress associated with worse probability of attempting suicide and with earlier age at onset of BD. Exposure to early stress correlated with GM volumes in the right prefrontal cortex (Brodmann area 46) – again, in *s carriers only. Conclusions 5‐HTTLPR modulated the relationship between early life stress and the core features of bipolar illness. 5‐HTTLPR*s carriers showed a higher sensitivity to the effects of stress; when exposed to low levels of early stress, they were protected against suicide in respect to l/l, but higher levels of stress progressively increased their risk of suicide and reduced the age at onset of illness.